Tuned in: Musical rhythm and social skills in adults. (March 2021) - Loeb, David; Reed, Jessa; Golinkoff, Roberta Michnick; Hirsh-Pasek, Kathy
In music, we "feel the beat" through rhythm. During successful social interactions, individuals establish an interpersonal rhythm through back-and-forth exchanges. Consequently, these two disparate domains share a common reliance on rhythm. This study investigates whether our sense of musical rhythm relates to our social competence. Ninety-eight undergraduate students ( M = 20.9 years, SD = 2.8 years) participated in a rhythm reproduction task and completed Riggio's Social Skills Inventory to examine whether the two skills are related. Scores on the rhythm task predicted participants' scores on one part of the inventory – the Social Control subscale – which measures how well individuals can adjust and adapt to different social exchanges. Critically, performance on the musical rhythm task did not correlate with every social subscale but only with that related to social exchanges. The results suggest that a core rhythmic ability might underpin performance in both musical and social domains.